2006
DOI: 10.1172/jci25422
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against citrullinated proteins enhance tissue injury in experimental autoimmune arthritis

Abstract: Antibodies against citrullinated proteins are specific and predictive markers for rheumatoid arthritis although the pathologic relevance of these antibodies remains unclear. To investigate the significance of these autoantibodies, collagen-induced arthritis (CIA) in mice was used to establish an animal model of antibody reactivity to citrullinated proteins. DBA/1J mice were immunized with bovine type II collagen (CII) at days 0 and 21, and serum was collected every 7 days for analysis. Antibodies against both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
388
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(412 citation statements)
references
References 52 publications
17
388
2
5
Order By: Relevance
“…The exact events leading to the formation of these antibodies are thus far unknown, as are the mechanisms by which they may contribute to tissue damage and inflammation. However, anti-CCP antibodies have been shown to aggravate collagen-induced arthritis in mice, which suggests that anti-CCP can be pathogenic (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The exact events leading to the formation of these antibodies are thus far unknown, as are the mechanisms by which they may contribute to tissue damage and inflammation. However, anti-CCP antibodies have been shown to aggravate collagen-induced arthritis in mice, which suggests that anti-CCP can be pathogenic (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ACPAs in patients with recent-onset RA is predictive for progression to erosive RA (10,11), and their presence in patients with undifferentiated arthritis is highly predictive of progression to RA (12). Likewise, ACPAs were shown to contribute to disease progression in a mouse model of arthritis (13). Taken together, data from human and mouse studies indicate that ACPAs are a possible pathogenetic mechanism in RA.…”
mentioning
confidence: 89%
“…In the past decade, considerable interest was devoted to autoantibodies against citrullinated proteins, proteins in which the amino acid arginine is posttranslationally modified to the nonstandard amino acid citrulline. In mice, it has been shown that infusion of ACPAs into animals with arthritis leads to exacerbation of arthritis, whereas a reduction in ACPA levels is associated with a less severe disease (9). These data indicate that ACPAs are directly involved in the progression of arthritis, but that they are not endowed with the capacity to induce arthritis in healthy hosts.…”
Section: Autoantibodiesmentioning
confidence: 99%